NMR and protein dynamics - Smith, L; Dobson, C (1996)
NMR techniques can give insight into a wide variety of motional events that occur in proteins over a range of timescales. In the first section of this article an overview of the results of dynamics studies, using NMR methods, on both small globular and larger multi-domain proteins is presented including the findings from investigations of non-native partly folded states. The second section of the article then concentrates on two topics where NMR can give residue specific quantitative data, namely coupling constant measurements and relaxation studies, including comparisons of these NMR data with results from crystallographic studies and theoretical molecular dynamics simulations. Finally the possible functional significance of the experimentally observed motions in proteins is discussed. © 1996 John Wiley and Sons, Inc.